Solid-state seeded nano-second pulse CO2 oscillator for extreme ultraviolet lithography - Nowak, Krzysztof M (Photonics Letters of Poland, 2013)
This Letter describes in some detail a novel, solid-state seeded, nano-second pulse, multi-line CO2 oscillator designed and built for the extreme ultraviolet (EUV) laser-produced-plasma (LPP) source. The oscillator employed quantum cascade laser (QCL) seeders, a spectral beam combiner and a diffusion-cooled, radio-frequency-discharge excited, slab-waveguide CO2 amplifier in a multi-pass and compact regenerative amplifier configuration. The output spectrum consisted of individually controlled laser lines of 0001-1000 band of a CO2 molecule, P18, P20 and P22 with a target 4-line operation (P18-P24). The resistance to self-seeding of more than 40dB and to the parasitic back-seeding of more than 55dB was realized. The oscillator produced up to 20W of average output power at repetition rate of 100kHz in a near-diffraction limited beam of M2 lower than 1.3 and RMS pointing stability below 50 microradians. Full Text: PDF References V. Bakshi, "EUV lithography", vol. 178 (SPIE Press, 2009). T. Ohta, K. M. Nowak, T. Suganuma, H. Kameda, M. Moriya, T. Yokoduka, Y. Kawasuji, J. Fujimoto, and H. Mizoguchi, "Development of the reliable high power pulsed carbon dioxide laser system for LPP EUV light source", Proc. SPIE 8322, 832220 (2012) CrossRef D. C. Brandt, I. V. Fomenkov, M. J. Lercel, B. M. La Fontaine, D. W. Myers, D. J. Brown, et al. "Laser produced plasma EUV sources for device development and HVM", Proc. SPIE 8322, 832246 (2012) CrossRef K. M. Nowak, T. Ohta, T. Suganuma, J. Fujimoto, H. Mizoguchi, and A. Sumitani, "CO2 laser drives extreme ultraviolet nano-lithography ? second life of mature laser technology", Opto-Electronics Review 21, 52 (2013). DirectLink K. M. Nowak, T. Ohta, T. Suganuma, J. Fujimoto, and H. Mizoguchi, "Multiline short-pulse solid-state seeded carbon dioxide laser for extreme ultraviolet employing multipass radio frequency excited slab amplifier", Opt. Lett. 38, 881 (2013). CrossRef K. M. Nowak, T. Ohta, T. Suganuma, T. Yokotsuka, J. Fujimoto, H. Mizoguchi, and A. Endo, "Spectral characteristics of quantum-cascade laser operating at 10.6 ?m wavelength for a seed application in laser-produced-plasma extreme UV source", Opt. Lett. 37, 4765 (2012). CrossRef K. M. Nowak, T. Ohta, T. Suganuma, T. Yokotsuka, J. Fujimoto, and H. Mizoguchi, "Wavefront measurement of single-mode quantum cascade laser beam for seed application in laser-produced plasma extreme ultraviolet system", Opt. Lett. 37, 4886 (2012). CrossRef